A LOW-TEMPERATURE KINETIC STUDY OF THE EXSOLUTION OF PENTLANDITE FROM THE MONOSULFIDE SOLID SOLUTION USING A REFINED AVRAMI METHOD - Wang H.; Ngothai Y.; O'Neill B.; Pring A. (My University, 2005)
A refined Avrami method, that assumes that the activation energy is a function of reaction extent y, was used to analyze the kinetics of the exsolution of pentlandite from mss/pyrrhotite (bulk composition, (Fe0.77Ni0.19)S) over the temperature range 473 to 573 K. The experimental results show the reaction rates vary from 1.6 × 10-5 to 5.0 × 10-7 s-1 at 473 K and from 9.4 × 10-5 to 4.1 ×-7 s-1 at 573 K. Examination of exsolution textures indicated that the mechanism of exsolution did not change significantly over the temperature range investigated. The activation energy (Ea) decreases from 49.6 to 20.7 kJ mol-1 over the course of the reaction. The decrease in Ea with y is related to the change in the dominant factor of pentlandite exsolution, from nucleation dominant at the beginning to metal ion diffusion dominant at the end. The classic Avrami method provides average values of kinetic parameters for the overall solid-state reaction while the refined Avrami method provides more a detailed indication of the variation of kinetic parameters over the course of the reaction. Previously published kinetic data for the exsolution of pentlandite from mss/pyrrhotite are reevaluated using the refined Avrami method. Copyright © 2005 Elsevier Ltd.
Keywords: exsolution kinetic; pentlandite